2020
DOI: 10.1088/1755-1315/548/8/082030
|View full text |Cite
|
Sign up to set email alerts
|

Functional fermented milk whey product: assessment of quality and safety

Abstract: The authors have developed a technology and a procedure for assessing quality and safety of a fermented milk whey product enriched with spirulina, tarragon, mint, and stevia sweetener used as a balanced complex of biologically active substances. Sensory quality indicators were assessed on a 5-point scale, using the profiling method. The taste panel analysis results showed that the enriched product had improved sensory properties and more pleasant harmonious taste and aroma. The examination of the chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Other authors have demonstrated that the administration of lactoferrin, an iron-binding glycoprotein in milk [ 41 ], does not lead to deaths or any adverse effects on the general condition of the animals. The antifungal activity of goat milk whey hydrolysate was determined against 10 toxigenic fungi from the genus Penicillium, in solid and liquid media in order to use as an ingredient for bread elaboration [ 42 ]. Following this line, even other researchers examined how to enhance milk whey by incorporating plant ingredients to create products with elevated sensory characteristics, heightened nutritional and biological values, as well as improved safety.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have demonstrated that the administration of lactoferrin, an iron-binding glycoprotein in milk [ 41 ], does not lead to deaths or any adverse effects on the general condition of the animals. The antifungal activity of goat milk whey hydrolysate was determined against 10 toxigenic fungi from the genus Penicillium, in solid and liquid media in order to use as an ingredient for bread elaboration [ 42 ]. Following this line, even other researchers examined how to enhance milk whey by incorporating plant ingredients to create products with elevated sensory characteristics, heightened nutritional and biological values, as well as improved safety.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main by-products troublesome in management is sweet whey produced in the cheese-making process (Rocha and Guerra 2020 ). It is usually re-used in the food industry, e.g., to produce special-purpose dietary foods and high-protein supplements (Slozhenkina et al 2020 ). The most popular whey processing methods include lactose removal by nanofiltration, demineralization via ionic exchange, or demineralization by electrodialysis, fractionation by membrane filtration, isolation of components by ionic exchange, concentration, evaporation, or drying (Wen-Qiong et al 2019 ; Smykov 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment of dairy products with natural ingredients, containing a considerable amount of essential nutrients, is used to develop the technology of fermented milk products. Spirulina, chickpea, St. John's wort, tarragon, mint, sage, stevia, chili pepper, black pepper, cinnamon, allspice, thyme, cumin and many others are used as additives [25][26][27][28][29]. Use of these spicy and aromatic additives improves and diversifies the taste and aromatic properties of fermented products, enrich them with biologically active substances, increase their stability when stored.…”
Section: Introductionmentioning
confidence: 99%